(untitled) (Archive of Conferences, 2022)
The problems of increasing the wearing capability and longevity of materials of working mechanisms of technological machines are highly actual. Defining importance in forming the features of constructive toughness of materials of working mechanisms of technological machines has, as is well known, variation of the structured condition. For this purpose article is studied structured conversions of steel under different types of the thermal processing, which vastly affect the specified characteristics